Hepatitis C infection and clearance: impact on atherosclerosis and cardiometabolic risk factors. Issue 8 (28th June 2010) - Mostafa, Aya; Mohamed, Mostafa K; Saeed, Mohamed; Hasan, Abubakr; Fontanet, Arnaud; Godsland, Ian; Coady, Emma; Esmat, Gamal; El-Hoseiny, Mostafa; Abdul-Hamid, Mohamed; Hughes, Alun; Chaturvedi, Nish
Abstract : Background: Chronic hepatitis C (HCV) infection is associated with diabetes and favourable lipids. Objective: To study the effect of this paradox on atherosclerosis and cardiometabolic response to HCV clearance. Design: Cross-sectional study. Setting: Egypt. Participants: 329 chronically infected, 173 with cleared infection and 795 never infected participants aged ≥35 attended for baseline investigations. A subsample of 192, 115 and 187, respectively, underwent ultrasound. Main outcome measures: Diabetes, fasting glucose, lipids and fat deposition on ultrasound. Carotid intima-media thickness (IMT) measured atherosclerosis. Results: Diabetes prevalence was raised (10.1% (95% CI 6.6 to 13.6), p=0.04) in HCV chronic, and cleared (10.1% (5.6 to 14.8), p=0.08) individuals versus 6.6% (4.9 to 8.3) in those never infected. Mesenteric fat was raised in chronic (36.4 mm (34.5 to 38.2), p=0.004), and cleared infection (37.8 (35.6 to 40.0), p<0.0001) vs never infected (32.7 (31.0 to 34.4)). LDL cholesterol was lower in chronic (2.69 mmol/l (2.53 to 2.86), p<0.001), but similar in cleared (3.56 (3.34 to 3.78), p=0.4) versus never infected (3.45 (3.30 to 3.60)). Carotid IMT did not differ by infection status: 0.73 (0.70 to 0.76, p=0.4), 0.71 (0.66 to 0.75, p=0.9), 0.71 (0.68 to 0.74), respectively. Adjustment for cardiovascular risk factors increased IMT in chronic infection (0.76 (0.72 to 0.79), p=0.02) versus never infected individuals (0.70 (0.67 to 0.73)). Conclusions: Hepatic function normalisation with HCV clearance may account for reversal of favourable lipids observed with HCV infection. Hyperglycaemia and visceral adiposity appear less amenable to HCV resolution. These different cardiovascular risk patterns may determine equivalent atherosclerosis risk by infection status. However, once these factors were accounted for, those with chronic infection had raised IMT, suggesting a direct effect of infection.